Unveiling the paradigm shift: systemic treatment strategies in small, node-negative breast cancer - Mariana Carvalho Gouveia; Mariana Scaranti; Bruna Migliavacca Zucchetti; Renata Colombo Bonadio; Romualdo Barroso-Sousa; Jose Pablo Leone (npj Breast Cancer)
Abstract The implementation of screening mammography has significantly altered the size distribution of breast tumors, with approximately 20% of newly diagnosed breast cancers measuring 10 mm or smaller with node-negative disease (T1aN0 and T1bN0). The management of these early-stage breast cancers remains a subject of debate. Historically, patients with T1aN0 and T1bN0 breast cancer have been excluded from adjuvant chemotherapy trials due to their excellent prognosis, with reported 10-year disease-specific survival rates exceeding 90%. However, the optimal treatment strategy for this subgroup of patients continues to be controversial, as the potential benefits of adjuvant chemotherapy must be carefully weighed against the risks of overtreatment. In this review, we summarize current evidence on outcomes and treatment strategies, highlight gaps in the literature, and provide future perspectives on the management of T1aN0 and T1bN0 breast cancer, according to immunohistochemical subtypes.